Capacidade tecnológica em sistemas agroindustriais: proposição de índice e aplicação a empresas dos segmentos de trigo e leite - Mori, Cláudia de (2010)
The technological capabilities play a crucial role in determining the production processes efficiency and effectiveness and increase the degree of enterprises innovativeness. Its measurement can help enterprises evaluate their strengths and weaknesses in terms of their ability to generate, use and adapt technologies and products, that is, it can assist them understanding the enterprise technological behavior and potential and serving as a diagnosis and decision making system. This project aimed to develop a technological capability measurement model (index) directed at agri-food systems. The developing of index model is applied on farms and agro-industrial enterprises of production chains of a plant segment (wheat grain, wheat flour/ premixture and pastry) and of an animal segment (fluid milk and cheese). The methodology adopted for this purpose has a deductive and theoreticalinstrumental character. The study made use bibliographical review and exploratory research for building indexes architectures and observational research to collect data to validate the proposed index model. The model proposes the measure of the entreprise technological capability stage based on five macroelements: (i) physical resources, (ii) technological upgrading, (iii) processes and routines, (iv) learning mechanisms and (v) coordination and accessibility. This macroelements are decomposed into meso and microelements. The descriptors include numerical, binary and categorical variables. The AHP method was used to assign indicators weights. To evaluate the proposed índex, interviews with farms and agro-industrial were conducted, totaling 200 farms and 19 enterprises. In general, the proposed index capture inter-firm differences in terms of technological capacity performance and serve as an analytical tool to generate useful information for identifying improvement opportunities for the company. It also captures the technological dynamic differences between companies and between regions.